2016
DOI: 10.3389/fnhum.2016.00616
|View full text |Cite
|
Sign up to set email alerts
|

Functional Connectivity Reveals Which Language the “Control Regions” Control during Bilingual Production

Abstract: Bilingual studies have revealed critical roles for the dorsal anterior cingulate cortex (dACC) and the left caudate nucleus (Lcaudate) in controlling language processing, but how these regions manage activation of a bilingual’s two languages remains an open question. We addressed this question by identifying the functional connectivity (FC) of these control regions during a picture-naming task by bimodal bilinguals who were fluent in both a spoken and a signed language. To quantify language control processes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 61 publications
3
4
0
Order By: Relevance
“…As a minor difference between the groups, we found more frequent activation of secondary language areas in bilinguals. This result aligns with previous studies that demonstrated that the left Caudate and Angular Gyrus are relatively more involved with bilingualism 41 , 42 .…”
Section: Discussionsupporting
confidence: 93%
“…As a minor difference between the groups, we found more frequent activation of secondary language areas in bilinguals. This result aligns with previous studies that demonstrated that the left Caudate and Angular Gyrus are relatively more involved with bilingualism 41 , 42 .…”
Section: Discussionsupporting
confidence: 93%
“…As a minor difference between the groups, we found more frequent activation of secondary language areas in bilinguals. This result aligns with previous studies that show that the left Caudate and Angular Gyrus is relatively more involved with bilingualism [4,5].…”
Section: Common Networksupporting
confidence: 93%
“…The activation of the DLPFC is deemed maximal when the subject is asked to switch between the known languages [4] and the BG may actively mediate signaling to the prefrontal cortex according to the changing target language being used by the subject at any given time. Specifically, the caudate may regulate the selection of the less accessible language [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bundles connecting modern language processing areas seem to have evolved within the main pathways from the visual areas to the prefrontal cortex; thus, visual stimuli may interfere more with the functioning of areas that are now commonly associated with language processing but also other tasks [ 15 , 16 ]. In addition, involvement through central areas is indicated [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%